Pre-season physical fitness model for junior middle-distance runners at excellence training stage - Inozemtseva, E. S.; Zemlyakova, Z. S. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to develop and test benefits of a new pre-season physical fitness model for junior middle-distance runners at the excellence stage as complementary to the regular training service.